State-Level Data on Suicide Mortality During COVID-19 Quarantine: Early Evidence of a Disproportionate Impact on Racial Minorities. (January 2021) - Mitchell, Thomas O.; Li, Luming
Highlights: The age-adjusted rate of completed suicides decreased 13% in Connecticut during the period of strict stay-at-home COVID-19 quarantine. The proportion of suicide decedents from racial minority groups significantly increased during the lockdown period. Further study of completed suicides during and after the pandemic is needed, with exploration of the role of race on suicide trends. Abstract: The unprecedented impact of COVID-19 has raised concern for the potential of increased suicides due to a convergence of suicide risk factors. We obtained suicide mortality data to assess completed suicides during the period of strict stay-at-home quarantine measures in Connecticut and compared this data with previous years. While the total age-adjusted suicide mortality rate decreased by 13% during the lockdown period compared with the 5-year average, a significantly higher proportion of suicide decedents were from racial minority groups. This finding may provide early evidence of a disproportionate impact from the social and economic challenges of COVID-19 on minority populations.